Exploration of the Required Clinical Competencies for Training General Practitioners to Acquire Social Accountability: A Qualitative Study - Yousef Adib; Eskandar Fathiazar; Mahasti Alizadeh; Gholamali Dehghani (Zanjan University of Medical Sciences and Health Services, 2018)
Background & Objective: Social accountability is an important and essential notion in medical training. Despite significant similarities, various countries have aimed to define proper competencies in medical education according to their own healthcare provision system and society needs. This study aimed to explore the required clinical competencies for training general practitioners to acquire social accountability. Materials and Methods: This study was conducted in Tabriz University of Medical Sciences, Tabriz, Iran in 2017 using qualitative content analysis. In total, 14 professors and five general practitioners were selected via purposive sampling, using their experiences and views until reaching information saturation stage. Data were collected and analyzed using a semi-structured interview and conventional content analysis, respectively. Results: In this research, six primary categories of "ability to provide clinical services based on a holistic approach", "cooperation with healthcare team members to promote health and prevention", "role playing in the healthcare system", "communication skills", "professional commitment and ethics", and "decision making in extreme conditions", In total, 15 subcategories were obtained. Conclusion: According to the results of this study, medical schools must train graduates who can be active in promotion of society health and committed to professional behaviors and ethics, effective communication, teamwork, performing primary care, improving health and preventing diseases in the whole society, which can result in the development of social accountability in medical training.